2023
DOI: 10.3390/foods12142809
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Ginseng Insoluble Dietary Fiber by Enzymatic Method: Structural, Rheological, Thermal and Functional Properties

Abstract: In this study, the effects of enzymatic modification using cellulase/xylanase on the composition and structural and functional properties of ginseng insoluble dietary fiber (G-IDF) were evaluated. Fourier transform infrared spectroscopy and scanning electron microcopy showed that enzymatic extraction treatment caused obvious structural alterations in ginseng-modified (G-MIDF) samples, which exhibited more porous and completely wrinkled surfaces. Comparing the peak morphology of G-MIDF with untreated IDF using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Meanwhile, ginseng oil contains not only ginsenosides but also various components such as aromatic compounds, carbohydrates, and proteins. Therefore, in the ginseng oil spectrum, strong peaks appeared at 2923 cm −1 (C-H stretching), 2852 cm −1 (stretching vibration of the -CH 2 -groups), and 1742 cm −1 (stretching vibration of the C=O group in volatile oils and other carbonyl-containing compounds) [39]. Notably, oils are characterized by strong characteristic peaks in FT-IR spectra.…”
Section: Characteristics Of the Fabricated Ginseng Microcapsulesmentioning
confidence: 97%
“…Meanwhile, ginseng oil contains not only ginsenosides but also various components such as aromatic compounds, carbohydrates, and proteins. Therefore, in the ginseng oil spectrum, strong peaks appeared at 2923 cm −1 (C-H stretching), 2852 cm −1 (stretching vibration of the -CH 2 -groups), and 1742 cm −1 (stretching vibration of the C=O group in volatile oils and other carbonyl-containing compounds) [39]. Notably, oils are characterized by strong characteristic peaks in FT-IR spectra.…”
Section: Characteristics Of the Fabricated Ginseng Microcapsulesmentioning
confidence: 97%
“…Epidemiological research conducted on humans and animals has demonstrated that DFs, which are non-starch polysaccharides, exhibit several significant biological properties ( Jiang et al, 2023 ; Jiang, Wu, Ameer, Li, & Ramachandraiah, 2020 ). Among the various health benefits, soluble dietary fiber (SDF) is known to enhance viscosity, lower blood sugar levels, and increase plasma cholesterol.…”
Section: Introductionmentioning
confidence: 99%